Biocompatibility and osteogenesis of the castor bean polymer doped with silica (SiO2) or barium titanate (BaTiO3) nanoparticles - Nacer,Renato Silva (2015)
PURPOSE:To evaluate the biocompatibility and osteogenesis of castor oil polymer doped with SiO2 or BaTiO3 nanoparticles.METHODS: Twenty four male rats Wistar were submitted to bone defect filled with castor oil polymer. The animals were distributed in two experimental groups had been formed with 12 animals each: Group 1 - Castor oil polymer doped with 0.30 grams of SiO2 replacing 0.30 grams of CaCO3. Group 2 - Castor oil polymer doped with 0.30 grams of BaTiO3 replacing 0.30 grams of CaCO3. Euthanasia occurred 30 and 60 days after surgery and the femurs were sent to histological analysis and MEV.RESULTS:The implants were biocompatible and allowed for progressive osteogenesis through osteoconduction in both observation periods. There was significant bone neoformation at 30 and 60 days in both groups within the histomorphometric evaluation, but group 1's osteogenesis was lesser in the 30 and 60-day periods observed when compared to the animals of group 2. The MEV morphometric evaluation evidenced a lesser percentage of osseous tissue filling within the BaTiO2-doped polymer.CONCLUSION:The castor oil polymer doped with SiO2 or BaTiO3 remained biocompatible and allowed for progressive osteogenesis in both observation periods.